Case report: hepatic arterial infusion chemotherapy combined with sintilimab and lenvatinib for conversion therapy of colorectal cancer liver metastases - Peng, Kai; Li, Yuhua; Su, Hao; Lan, Chenlu; Huang, Zaida; Wei, Yongguang; Liao, Xiwen; Peng, Minhao; Peng, Tao; Zhu, Guangzhi (Frontiers in Immunology, 2023)
Background: Liver metastasis is one of the most common causes of death in patients with colorectal cancer. Therefore, improving the treatment effect of liver metastatic carcinoma of colorectal cancer is also one of the effective ways to improve the survival time of patients with colorectal cancer. The main treatment method for liver metastasis of colorectal cancer is preoperative neoadjuvant chemotherapy through intravenous administration. However, no one has reported a conversion therapy approach for the treatment of colorectal cancer liver metastases patients through arterial infusion chemotherapy combined with targeted agents and PD-1 monoclonal antibody. This case reports a conversion therapy method of liver metastases of colorectal cancer by hepatic arterial infusion chemotherapy(HAIC), Sintilimab Injection combined with Lenvatinib to achieve radical resection of liver metastatic carcinoma after treatment. Case presentation: The patient was a 69-year-old man who had previously undergone laparoscopic left hemicolectomy for descending colorectal cancer and multiple interventional and surgical treatments for hepatocellular carcinoma. During this treatment, the patient underwent radiological and serological tests, and primary liver cancer was considered at the initial diagnosis stage. Therefore, this liver malignant tumor lesion was treated according to the primary liver cancer treatment protocol before surgical resection. Therefore, the patient received hepatic arterial infusion chemotherapy (HAIC) combined with Sintilimab Injection and Lenvatinib. After three treatment cycles, radiological examination showed no obvious tumor activity, alpha-fetoprotein (AFP) decreased to normal, protein induced by vitamin K absence or antagonistⅡ, (PIVKA II) decreased significantly, and the curative effect was evaluated as complete remission. Subsequently, we performed surgical resection of this liver lesions. The pathological response of left lobe tumor was partial remission (PR). Most of the tumors were necrotic and the necrosis rate was greater than 95%. A small amount of live tumor tissue remains (<5%). The pathological classification of this tumor was confirmed as moderately differentiated adenocarcinoma by immunohistochemical staining of multiple tumor indicators in the pathology department. No significant adverse drug events were observed in this patient during treatment. Conclusion: Hepatic arterial infusion chemotherapy combined with Sintilimab Injection and Lenvatinib conversion therapy therapy provides the opportunity for radical surgical resection of colorectal cancer liver metastases.